2010
DOI: 10.1007/s10591-010-9136-0
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Spirituality in Couple and Family Therapy: A Comparative Study of Therapists’ and Educators’ Beliefs

Abstract: The purpose of this study was to explore the differences between the beliefs of couple and family therapists (CFTs) and CFT educators in accredited training programs regarding the importance of spirituality in their personal and professional lives. The results suggest a significant difference between the two populations, with clinicians reporting a higher level of agreement regarding the overall role of spirituality in their personal and professional identities compared to CFT faculty members. However, both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…It has been reported that engaging in personal spiritual exploration is associated with increased use of spiritual integration activities in therapy and this proves to be true with our study. While MFT faculty surveyed reported that a course solely dedicated to spiritual integration was not needed (Carlson et al, 2011), our study demonstrates that specific training in this area increases student comfort with and frequency of engaging in these essential conversations (Lyness, Haddock, & Zimmerman, 2003). Most importantly, spirituality is often important to clients and is an aspect of diversity that is neglected in MFT training.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…It has been reported that engaging in personal spiritual exploration is associated with increased use of spiritual integration activities in therapy and this proves to be true with our study. While MFT faculty surveyed reported that a course solely dedicated to spiritual integration was not needed (Carlson et al, 2011), our study demonstrates that specific training in this area increases student comfort with and frequency of engaging in these essential conversations (Lyness, Haddock, & Zimmerman, 2003). Most importantly, spirituality is often important to clients and is an aspect of diversity that is neglected in MFT training.…”
Section: Resultsmentioning
confidence: 81%
“…While the definition of spirituality is personal to each individual, in this article we consider spirituality an umbrella term that refers to a dimension of life that provides meaning‐making, purpose, and perspective to people who identify as religious, spiritual, both, or neither (Anderson & Worthen, ; Aponte, ; Prest & Keller, ; Walsh, ). In addition, spirituality is part of systemic practice (Larner, ; Telfener, ) as it comprises an important aspect of many people's lives, influences their relationship systems, and promotes growth and resilience (Carlson, McGeorge, & Anderson, ; Nedumaruthumchalil, ; Walsh, ). MFTs have emphasized the importance of addressing spirituality in therapy and advocated for training in this area for over two decades (Fife & Whiting, ; Haug, ; Helmeke & Sori, , ; Marterella & Brock, ; Stander, Piercy, Mackinnon, & Helmeke, ; Wendel, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Searching through public databases, a great part of the existing (English language) research in this field consists of evaluations of the integration of spirituality and religion in family therapy education in the US. Family therapy programs in the US currently include spirituality and religion in their courses of education, but there are discrepancies between faculties, clinicians, and students regarding the importance of integration of religion/spirituality in the programs (Carlson et al., ; McInnes Miller, & Van Ness Sheppard, ; Weinstein & Chicago, ).…”
Section: What Does the Literature Say?mentioning
confidence: 99%
“…Spirituality is an important part of many clients’ lives, but has been absent in family therapy research and theory (Carlson, McGeorge, & Anderson, ; Walsh, , ). However, in the last two decades, many family therapists and researchers have highlighted the importance of including spirituality and religion in therapeutic dialogue with clients.…”
mentioning
confidence: 99%